The financial & non-financial determinants on Grover's financial difficulty model - Ivanne, Queen Fiona; Radianto, Wirawan Endro Dwi (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2024)
BPS data showed that IDXNONCYC stocks dominated by the food & beverage companies were the most affected sector by the pandemic. This research aims to investigate the effects of financial & non-financial determinants, namely leverage (DER), liquidity (CR), & company’s age on Grover’s financial difficulty model of IDXNONCYC companies for the 2020-2022 period affected by pandemic with company’s size as a control variable. The research population is all primary consumer goods (IDXNONCYC) companies listed on the official IDX website for the 2020-2022 period, totaling 375 company-year data as objects. A sample of 237 observations were selected using purposive technique. The stages of research analysis are descriptive statistics, classical assumption & multiple regression testing. The data was analyzed through STATA software. This research provides evidence that DER, CR & company’s age have a strong effect on financial difficulty. All hypotheses of this research are accepted. This research pioneered the investigation of the effects of financial and non-financial determinants on Grover’s financial difficulty model. Theoretically, this research has implications for the development of financial difficulty determinants theory. Practically, this research has implications for investor decision-making in the capital market and companies to prevent bankruptcy